Technological touch initiative on waste management in TPST 3R Mulyoagung Bersatu to realize clean earth green future - Iis Siti Aisyah; Moch Syamsul Ma arif; Erna Retna Rahadjeng (Universitas Muhammadiyah Malang, 2025)
Waste management remains a significant challenge in many communities, particularly in urban areas, where densely populated housing is prevalent, and improper disposal can lead to environmental damage and health risks. . In response to this, the concept of an Integrated Waste Processing Facility (TPST), established in Mulyoagung Village, Dau District, emerged as a sustainable solution. However, the Dau TPST Management faces the problem of not having a special waste sorting machine, making the TPST's performance ineffective, as it still relies on manual waste sorting activities carried out by women worker, which poses a risk to health risks. Also, TPST still rely on traditional marketing in selling their product. Therefore the aims of the community service is assisting TPST to provide the appropriate waste sorting machine and e-commerce platform. The method implemented in the community service is started by situational analysis of the target, design and manufacturing of waste sorting machines for organic and non-organic waste, built prototype and to test the functionality in a controlled setting, provide training for staff on machine operation and maintenance, integrate with existing workflows, and monitor the performance of machine. The e-commerce assistance was conducted by giving training in e-commerce and community awareness to waste management. The result of the program is positive both in sorting machine application and e-commerce and awareness as concluded from the survey before and after the program.